2020
DOI: 10.3389/fphys.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Rest, Rather Than Activity, Underlies Day-Night Activity Differences in Mice

Abstract: The suprachiasmatic nucleus (SCN), which serves as the central pacemaker in mammals, regulates the 24-h rhythm in behavioral activity. However, it is currently unclear whether and how bouts of activity and rest are regulated within the 24-h cycle (i.e., over ultradian time scales). Therefore, we used passive infrared sensors to measure temporal behavior in mice housed under either a light-dark (LD) cycle or continuous darkness (DD). We found that a probabilistic Markov model captures the ultradian changes in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…While small homecages can present some challenges, accuracy is still high and PRT has not only demonstrated capabilities to chronically track multiple mice from minutes to days, but also detect underlying animal phenotypes (stroke). Consistent with other studies, chronic recordings in the modified home-cage revealed diurnal locomotor activity patterns in mice (Ananthasubramaniam and Meijer, 2020; Wang et al, 2019). Specifically, mice showed higher levels of distance traveled, turns made, travel speed, and duration being active at night compared to day cycles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While small homecages can present some challenges, accuracy is still high and PRT has not only demonstrated capabilities to chronically track multiple mice from minutes to days, but also detect underlying animal phenotypes (stroke). Consistent with other studies, chronic recordings in the modified home-cage revealed diurnal locomotor activity patterns in mice (Ananthasubramaniam and Meijer, 2020; Wang et al, 2019). Specifically, mice showed higher levels of distance traveled, turns made, travel speed, and duration being active at night compared to day cycles.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 4 cages each containing 3 mice were recorded for three days using the modified home-cage illustrated in Fig 3A . The effects of day/night cycle (lights on and lights off) on dependent outcomes such as distance traveled, active duration, average speed, wide angle turn count, sharp angle turn count, and average acceleration along with anxiety measures such as duration spent in the center, interacting with one or two mice were determined using an MANOVA (Seibenhener and Wooten, 2015). As expected, mouse activity levels follow a reverse circadian rhythm (Ananthasubramaniam and Meijer, 2020).…”
Section: Chronic Tracking In Custom Home-cagementioning
confidence: 99%
“…GluA1 knockouts’ extended active period but reduced total wheel-running activity may seem paradoxical, but it could be related to changes in overall circadian parameters, for example reduced robustness of the ~24-h rhythm; it could also be the result of altered microstructure of activity and rest [ 69 ], such as changes in activity/sleep bout length due to activity/sleep fragmentation. These possibilities were thoroughly investigated below.…”
Section: Resultsmentioning
confidence: 99%